Fire Safety Technology Related to Building Design and Construction - Chow, W.K. (International Journal of Integrated Engineering, 2013)
Fire safety technology related to building design and construction will be discussed in this paper. Four areas on possible fire hazards and fire safety provisions; performance-based design; flawed concept of timeline analysis; water suppression system in atrium including sprinkler and its alternatives with water gun and sidewall long-throw sprinklers are reported. The proposed annual inspection scheme on the design criteria in fire safety design to ensure assumptions made in the fire safety assessment by the Hong Kong Fire Services Department should serve as an example of good practice.